2019
DOI: 10.1016/j.jcrysgro.2019.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Thin Ge buffer layer on silicon for integration of III-V on silicon

Abstract: Development of Si-based lasers is considered as the key to the realization of fully integrated Si photonic circuits. Monolithic growth of III-V lasers on Si substrates is one of the most promising solutions for developing a commercially viable Si-based laser. However, the performances of current devices are still hindered by defects, hence the optimisation of crystal quality of the laser structures is of paramount importance. This paper reports on growth optimisation of thin Ge buffer layers on Si as an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Hayafuji et al [ 321 ] reported that the mechanism behind SLs effect is the hardening of crystal and bending of dislocation along the superlattice interface. In addition, growth of buffer layer of Ge with high epitaxial quality, [ 322 , 323 ], LT/HT epitaxy (see Figure 46 a), and CMP are popular methods to control the propagation of misfit dislocations, as shown in Figure 46 b [ 324 ].…”
Section: Iii-v Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayafuji et al [ 321 ] reported that the mechanism behind SLs effect is the hardening of crystal and bending of dislocation along the superlattice interface. In addition, growth of buffer layer of Ge with high epitaxial quality, [ 322 , 323 ], LT/HT epitaxy (see Figure 46 a), and CMP are popular methods to control the propagation of misfit dislocations, as shown in Figure 46 b [ 324 ].…”
Section: Iii-v Materialsmentioning
confidence: 99%
“…with high epitaxial quality, [322,323], LT/HT epitaxy (see Figure 46 (a)), and CMP are popular methods to control the propagation of misfit dislocations, as shown in Figure 46 (b) [324].…”
Section: Global Epitaxymentioning
confidence: 99%
“…Because the cracks were preferentially formed at the edges of the notches acting as stress concentrators, the periodic crack arrays could be achieved, resulting in a crack-free region (2 × 2 mm 2 ) where 5.8 µm-thick GaAs-based solar cell structures were grown. Recently, instead of a thick GaAs buffer layer, growing a thin Ge layer on Si was proposed [143,247]. For example, Yang et al [143] demonstrated that although a 300 nm-thick thin Ge layer replaced the conventional 1 µm-thick GaAs buffer layer for InAs/GaAs QD lasers on Si, the fabricated lasers with thin Ge buffer showed comparable performances, in terms of TDD and lasing behavior, to the conventional QD lasers with thick GaAs buffer.…”
Section: Minimizing Thermal Cracksmentioning
confidence: 99%
“…Note that the growth conditions were identical for both samples during the growth of all subsequent layers. The laser structure is shown schematically in Figure 1, containing an optimised 300 nm Ge/Si VS [39]. The growth started with a three-step growth technique for the thin Ge layer.…”
Section: Crystal Growth and Device Fabricationmentioning
confidence: 99%